The influence of sodium supplementation on the voluntary intake and digestibility of low-sodium Setaria sphacelata Nandi by cattle - Little, D.A. (Cambridge University Press, 1987)
This study examines the effect of sodium (Na) supplementation on the intake and digestibility of Na-deficient feed by cattle, and the potential applicability of faecal analysis to the diagnosis of Na deficiency in the field. Mature cattle fitted with oesophageal fistulae were fed chaffedSetaria sphacelatacv. Nandi hayad libitumin metabolism cages, with and without a Na supplement (10 g Na daily as NaHCO3). In the first of two experiments the hay contained 0·44 g Na/kg D.M., and in the second, 1·05 g/kg. Prior to an unsupplemented treatment the animals were rapidly depleted of Na by removal of saliva via the fistula; Na status was assessed on the basis of the ratio Na/K in saliva.When the feed contained 0·44 g Na/kg, Na supplementation increased voluntary intake by 28% (P < 0·01) and digestibility by 12% (P <0·05). No such responses were obtained in Expt 2, in which the feed contained 1·05 g Na/kg.Examination of available data suggests that a diagnosis of Na deficiency in cattle is indicated if the faecal Na concentration is below 1 g/kg D.M., and the ratio Na/K in faeces is less than 0·1. Further data are required to confirm these criteria, which should prove useful in the field when samples of saliva, the diagnostic criterion of choice, are not available.